TECHNOLOGICAL CHANGE AND MANPOWER TRAINING IN NIGERIAN PUBLIC ORGANIZATIONS: A STUDY OF SELECTED PARASTATALS IN RIVERS STATE - EDWIN M, DAPPER,; DADDIE, JOEL, AUGUSTUS-; C, NWAJI, CHARLES (IJRDO - Journal of Business Management, 2017)
Technological Change And Manpower Training In Nigerian Public Organizations: A Study Of Selected Parastatals In Rivers State. The study followed the descriptive survey design, using a five point likert scale questionnaire to generate data. Purposive sampling was used to select 80 respondents from a population of 141 middle level manpower, from five selected state parastatals in Rivers-state. The data gathered was analyzed using the t-test with the aid of statistical package for social sciences (SPSS) 20.0 version. With 0.001, 0.002 and 0.000 as the result obtained from the three hypotheses in this study, it points to the fact technological change is breeding a paradigm in manpower training process especially as it affects process effectiveness, efficiency and post-training performance of the trainees. It was therefore concludes that for public sector manpower to maximize training opportunities in this dynamic technological age; there is need to acquire both rudimentary knowledge and skill in ICT. Again, to bridge post-training performance gap, trainings should be designed to align with the technology workers are expected to use in performing their task. This creates familiarity and expertise in the worker, thereby making knowledge transfer from training to actual work situation less herculean